Caracterización y Análisis de Factores Psicosociales de Reclusos del Pasillo A del Establecimiento Penitenciario y Carcelario de la Ciudad de Tuluá-Valle (2023)
The main objective of this research work was to analyze the most relevant psychosocial factors presented by the inmates treated in the psychology service of corridor A, of the INPEC Tuluá-Valle medium-security penitentiary and male prison. For the development of the research process, a detailed bibliographic review was carried out regarding the topic and subtopics related to the research problem.